Trade Openness and Economic Growth of Nepal: An Econometric Analysis - Neupane, Deepak (Journal of Business and Management, 2023)
Background: The relationship between trade openness and economic growth has been a subject of empirical investigation- a multifaceted and evolving issue in the context of Nepal which is a highly import-based economy. In this background, the results of the exploration of the relationship between trade openness and economic growth would be relevant to suggest that policymakers in adopting the policies and boosting the available capital and labour to attain the benefits of trade openness.Objectives: This study examines the impact of trade openness on the economic growth of Nepal considering GDP, human capital, real gross capital formation, and trade openness employing both descriptive and econometric methods.Methods: This study incorporated the annual time series data published by the government of Nepal from the year 1990 to 2021 and analyzed employing the vector error correction model (VECM) along with the descriptive analysis.Results: Descriptive statistics reveal that the model follows a normal distribution, as indicated by the results of JarqueBera, where the p-values of the variables exceed 0.05. The variables demonstrate stationary at the first order and are cointegrated as such vector error correction model (VECM) is employed. The presence of a negative and significant error correction term (ECT) indicates that the variables are adjusting towards long run equilibrium. Furthermore, the stability of the model is confirmed by the cumulative sum (CUSUM) test as the residual plots remain within acceptable boundaries of a 5 percent significance level. Finally, the results indicate that trade openness does not have a significant and pivotal influence on economic growth.Conclusion: Trade openness does not have a significant influence on economic growth. Capital has a significant and positive relationship with stimulating economic growth, however, human capital has a significant but negative relationship with economic growth in the long run in Nepal.